Critical Analysis of Language Shift: A Case Study of Young Learners in Teochew Chinese Community in Singapore - Hanlu Song (Journal of Advanced Research in Education, 2024)
This study critically explores the phenomenon of language shift among young learners in the Teochew Chinese community in Singapore during the 1990s. Using the framework of ethnolinguistic vitality (EV), it examines the factors contributing to the decline of the Teochew dialect and its replacement by a combination of Mandarin and English. The research identifies key drivers of this language shift, including the low social status of the Teochew dialect and limited institutional support, both formal (government policies and educational systems) and informal (family and cultural practices). The analysis reveals that the reduced use of Teochew among younger generations is closely tied to language policies promoting Mandarin and the prioritization of English in formal education. The findings highlight the necessity of revitalizing Teochew through targeted strategies, including reforming language policies to support multilingualism, integrating indigenous language education in schools, and encouraging greater use of Teochew within families. These interventions are essential for maintaining the linguistic and cultural identity of the Teochew community.